Advances in visual informatics third International Visual Informatics Conference, IVIC 2013, Selangor, Malaysia, November 13-15, 2013. Proceedings (Lecture notes in computer science, 2013)
This book constitutes the refereed proceedings of the Third International Conference on Advances in Visual Informatics, IVIC 2013, held in Selangor, Malaysia, in November 2013. The four keynotes and 69 papers presented were carefully reviewed and selected from various submissions. The papers focus on four tracks: computer visions and engineering; computer graphics and simulation; virtual and augmented reality; and visualization and social computing